Rural Digitalization Problematics in Indonesia - Mukhammad Akhmad Najich Alfayn; Abas Bahar A’rof (Program Studi Ilmu Pemerintahan, FISIP - Universitas Halu Oleo, 2023)
This study aims to determine the problems of village digitalization as an evaluation of village digitalization adoption in realizing good governance. At this time, the Indonesian government is implementing a national strategy for digital transformation, so it is hoped that this research will be able to provide insights or descriptions of how problematic the digitalization process is and how they adjust to certain aspects of the governance digitization process that are useful for assessing current digital policies. this and future policies. The method used in this research is qualitative method. The approach that researchers use is literature study. The results of this study indicate that the problem of village digitization lies in infrastructure gaps, digital mindset, and the quality of digitalization development. There needs to be a commitment from the village government for the development of e-government which is rooted in a change in work culture from traditional to electronic by utilizing information technology tools. Future research can focus on evaluating the village government's commitment to adjusting village digitization